Hate Speech Law A Philosophical Examination - Brown, Alex (Routledge Studies in Contemporary Philosophy, 2015)
Hate speech law can be found throughout the world. But it is also the subject of numerous principled arguments, both for and against. These principles invoke a host of morally relevant features (e.g., liberty, health, autonomy, security, non-subordination, the absence of oppression, human dignity, the discovery of truth, the acquisition of knowledge, self-realization, human excellence, civic dignity, cultural diversity and choice, recognition of cultural identity, intercultural dialogue, participation in democratic self-government, being subject only to legitimate rule) and practical considerations (e.g., efficacy, the least restrictive alternative, chilling effects). The book develops and then critically examines these various principled arguments. It also attempts to de-homogenize hate speech law into different clusters of laws/regulations/codes that constrain uses of hate speech, so as to facilitate a more nuanced examination of the principled arguments.